PENGARUH CERITA WAYANG SUKURAGA TERHADAP PENDIDIKAN KARAKTER SISWA DI KELAS TINGGI SEKOLAH DASAR - Nurul Amalia; Iis Nurasiah; Dyah Lyesmaya; Yoesrina Novia Vini Syafitri (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
This study aimed to determine the effect of the Sukuraga puppet story on the student’s character education in elementary schools. This study utilized a quasi-experimental type of quantitative approach. The design used in this research is the Nonequivalent Control Group Design. The subjects used in the study were 4 th -grade students of SDN Suryakencana CBM. The data collection tool in this study used a questionnaire using a Likert scale measurement consisting of 20 statements with the answers to statements including Always (SL), Often (SR), Sometimes (KK), Rarely (J), Never (TP). ) based on a checklist (√) on the attitude scale instrument grid. Based on the results of data processing pretest and posttest, with the calculation of the t-test carried out with the help of the IBM SPSS version software 26 with the results of planting character education using the Sukuraga puppet story, it obtained sig (2- tailed) 0.000 which is less than = 0.05. Based on the results from this calculation, it can be concluded that the story of the wayang Sukuraga affected the character education of students.